Mitigating the impacts of climate change on farmerherder conflicts in the Sahel - Flintan, Fiona E.; Ba, Baba; Orenstein, Alex (International Livestock Research Institute, 2025)
A presentation on mitigating the impacts of climate change on farmer-herder conflicts in the Sahel.